Q: What plus 73 equals -27?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

The number one rule is "what you do to one side, you must do to the other". So to demonstrate in detail: e - (-73) = -27 e - (-73) + 73 = -27 + 73 e = 46

It is: -73--27 = -46 because a double minus becomes a plus and --27 is the same as +27

65

B=61

s = negative 73 (-73)

Related questions

19 plus 54 equals 73. when you subtract like this x+19=73 X+19=73 -19 -73 0 54

118

73 + 27 = 100

The number one rule is "what you do to one side, you must do to the other". So to demonstrate in detail: e - (-73) = -27 e - (-73) + 73 = -27 + 73 e = 46

It is: -73--27 = -46 because a double minus becomes a plus and --27 is the same as +27

16 + (73%) = 27.68

65

B=61

s = negative 73 (-73)

73

-2402

16 plus 27 equals 43.